If We Build It, Will They Come? Perceptions of HIV Cure-Related Research by People Living with HIV in Four U.S. Cities: A Qualitative Focus Group Study - Sylla, Laurie (AIDS Res Hum Retroviruses, 2018)
Global interest and investment in the search for an HIV cure has increased. Research has focused on what experts refer to as a sterilizing or eradicating cure, where HIV is eliminated from the body, and on what is often called a functional cure, where HIV remains, kept durably suppressed in the absence of antiretroviral treatment and therapy (ART). Many believe that a functional cure is likely to be found first. HIV cure studies will require active participation by people living with HIV (PLWHIV). Their desires and perceptions will be important to effectively recruit study participants and for the uptake of any future strategy that demonstrates safety and efficacy. The perspectives of PLWHIV are essential to advancing HIV cure research, and they should be taken into consideration as biomedical research advances. We conducted 10 focus groups in four U.S. cities, eliciting perspectives of PLWHIV on HIV cure and cure research. Most participants conceived of a cure as eradicating, and felt favorably toward it. In addition to the physical benefits of a potential cure, participants valued the possible de-stigmatization related to no longer living with HIV, liberation from concerns about transmitting HIV, and freedom from the burden of daily medication. Many participants did not regard a functional cure as an improvement over controlling HIV through ART, were distrustful about viral rebound potential, and noted concerns about medical complications and accompanying psychological distress. Some felt that the risks of HIV cure research were not worth taking. Many were skeptical about science's ability to eliminate HIV from the body.